Analysis of Factors Influencing The Implementation of Public Safety Center Services Using Technology Acceptance Model and Unified Theory of Acceptance and Use of Technology Methods Among Pediatric Patients at Dr. Iskak Hospital, Tulungagung, East Java - Aini, Zuhrotul; Peristiowati, Yuly; Ellina, Agusta Dian (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: A pediatric emergency is a clinical situation with life-threatening risks without prompt and adequate management. The Public Safety Center (PSC) is the spearhead of the service to get a quick response and function as a service provider for emergency patients and to coordinate with the intended health facility. The purpose of this study was to analyze the factors that influence the implementation of the use of PSC services using the TAM and UTAUT methods in pediatric patients at RSUD dr. Iskak Tulungagung. Subjects and Method: Observational research was conducted at RSUD Dr. Iskak, Tulungagung, East Java from August to October 2022. A total of 130 children were selected for this study. The dependent variable is the implementation of the public safety center (PSC). The independent variables are the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). Data were collected using a questionnaire, and analyzed using path analysis. Results: Perceived benefits (p < 0.001), perceived convenience (p < 0.001) have a significant effect on PSC implementation. Work expectations (p= 0.068), business expectations (p= 0.436), and facilitating conditions (p= 0.106) are related to PSC implementation but not statistically significant. Conclusion: Perceived benefits, perceived convenience significantly influence the implementation of PSC. Keywords: child, emergency, PSC, TAM, UTAUT. Correspondence: Zuhrotul Aini. Master’s Program of Public Health, Strada Institute of Health Sciences, Indonesia. Jl. Manila No.37, Tosaren, Kec. Pesantren, Kota Kediri, Jawa Timur 64123. Email: ainizuhri74@gmail.com. Mobile: +62 812-3336-2126.